Textile antenna with simultaneous frequency and polarization reconfiguration for WBAN - Salleh, Shakhirul Mat; Jusoh, Muzammil; Ismail, Abdul Hafiizh; Kamarudin, Muhammad Ramlee; Nobles, Philip; Rahim, Mohamad Kamal A.; Sabapathy, Thennarasan; Osman, Mohamed Nasrun (Institute of Electrical and Electronics Engineers (IEEE), 2018)
This paper proposes the design of a reconfigurable circularly polarized textile antenna. The circular polarization feature in the proposed antenna is generated by the edge-truncation of a rectangular patch and the incorporation of a slotted ground plane, whilst the frequency re-configurability feature is realized by slot size modification via the use of three embedded RF PIN diode switches. Consequently, the antenna operation can be switched between six frequencies (1.57 GHz, 1.67 GHz, 1.68 GHz, 2.43 GHz, 2.50 GHz and 2.55 GHz) depending on the seven switch configurations. The proposed antenna is validated experimentally to be operable within the WBAN, WLAN and GPS range in a compact and wearable format, with gains of up to 4.8 dBi.